Jean Watson's Nursing Model Theory Concept: Caring Theory in Nursing Care for Patients with Diabetes Mellitus at Jakarta Cempaka Putih Islamic Hospital - Qiyan, Ain Atta; Nursanti, Irna (Jurnal KESANS : Kesehatan dan Sains, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by high blood glucose levels (hyperglycemia) due to impaired insulin secretion. From the nursing model, according to Jean Watson, nursing interventions are applied with ten characteristic factors. This article aims to improve the quality of the nurse-client relationship through the process of caring, encouraging holistic healing, both physical and spiritual. The method in the concept of Jean Watson's model theory is the quantitative method. Assess the perception of caring nurses or patients using quasi-experimental surveys. The impact on nurses Jean Watson's nursing intervention findings significantly improved empathy and humanity, nurses' emotional well-being, and improved therapeutic communication skills. Jean Watson's study recommendations in the future include the development of a caring model in the digital era and health technology related to the application of caring in telemedicine and the causative factor applied when interactions are not face-to-face.